Regional feature purification contrastive learning for wheat biotic stress detection - Chen, Junming; Chen, Yu-Xuan; Xu, Sheng-He (Frontiers in Plant Science, 2025)
The identification of wheat infections has always been a considerable problem in agricultural forecasting. This paper presents an automated classification framework for wheat illnesses utilising region feature purification contrastive learning, which combines unsupervised representation learning with label mutual information maximisation to improve feature extraction and classification efficacy. The integration of the W-Paste approach enhances the model’s resilience to input perturbations, hence augmenting its out-of-distribution detection efficacy. Additionally, the creation of a feature purification encoder enhances feature consistency by reducing interference via reverse learning, resulting in a significant improvement in classification accuracy. Attaining an average classification accuracy of 98.01% on public datasets illustrates the remarkable performance, efficacy, and resilience of our system in intricate situations. This study presents a novel and pragmatic approach for the automated identification of wheat illnesses, laying a robust groundwork for the progression of intelligent agriculture. The ongoing enhancement of the suggested framework is anticipated to advance the early detection and accurate diagnosis of wheat illnesses, hence promoting more effective crop management and sustainable agricultural development.